Analisis Penerapan Akutansi Dan Penggunaan Informasi Akutansi Pada UMKM (Studi Pada UMKM Binaan Dinas Koperasi Dan UMKM Kota Mataram) - Fatmawati; Ida Ayu Nursanty; Rusli Amrul (Akuntabel: Jurnal Ilmiah Akuntansi, 2025)
This research aims to determine the application of accounting records in micro, small and medium enterprises registered with the Mataram City Cooperatives and MSMEs Service and to determine the use of accounting information in micro, small and medium enterprises registered with the Mataram City Cooperatives and MSMEs Service. The method used in this research is to use the case study method by looking at developing phenomena, using data collection techniques using interviews and questionnaires, and documentation, data analysts in this research use the criteria method of using the criteria of personality and trust. The results of this research on the system for implementing accounting information systems in MSMEs in Mataram City have been carried out, and are still relatively low, the use of accounting information in MSMEs in Mataram City has been carried out. The use of accounting information is carried out at the cost level and making decisions about cash in and cash out.